Adopting Business Intelligence (BI) For Performance Monitoring Through USMIR - Yusoff, Ahmad Fadhlul Irham (2015)
Motivation for USM to continuously measure, monitor and improve the performance comes from various factors, mainly competition to acquire best student that contribute to the quality of researchers, research and publications, secure funding, accreditation, rating and status. USM tum to ICT with the formation of USMiR project, to have cohesive, useful and sustainable Information Repository regardless of platforms, routine operating procedures as well as bureaucracies. This case study looks into the factors that contributed to the failure of USMiR project to deliver its objectives. The study begins with understanding the current state pertaining to the data flow in USM, by using MyRA audit process as an example, for easier understanding. Also, it looks into KPI-MS online platform and USMiR architecture as well as standard operating procedure in placed. Current issues such as data/information mostly confined at every schools/PTJs or at particular database which is very time consuming to be gathered, lack of data and process integration poor solution architecture design and stakeholder momentum towards USMiR project were discussed. To further understand the potential root causes of those issues, a comprehensive analysis is performed using interview, reference of documents, Fishbone and Pareto analysis tools. The goal for this study is to understand and find a solution to the problems faced by USMiR in meeting its objective.